ChemInform Abstract: X‐Ray Crystallographic and First‐Principles Theoretical Studies of K2[TcOCl5] and UV/Vis Investigation of the [TcOCl5]2‐ and [TcOCl4]‐ Ions. Issue 47 (4th November 2013) - Johnstone, Erik V.; Weck, Philippe F.; Poineau, Frederic; Kim, Eunja; Forster, Paul M.; Sattelberger, Alfred P.; Czerwinski, Kenneth R.
Abstract K2[TcOCl5] is isolated as green single crystals by dissolution of (NH4)TcO4 in 12 M HCl at 0 °C and precipitation with KCl.